Toward an Imaginary Animal Studies: Review of Boria Sax, Imaginary Animals: The Monstrous, the Wondrous, and the Human - Iveson, Richard (Humanimalia, 2015)
Boria Sax, Imaginary Animals: The Monstrous, the Wondrous, and the Human. London: Reaktion Books, 2013. 278pp. 39.00 hb.